Makna psikologis zikir lata’if dalam transformasi kesadaran integratif santri ruhul a'zam : analisis fenomenologis - Saparudin Saparudin; Risydah Fadilah; Patisina Patisina (Jurnal EDUCATIO: Jurnal Pendidikan Indonesia, 2026)
This study aims to uncover the psychological significance of the practice of dzikir lata'if (recitation of God) in transforming the integrative consciousness of students at the Ruhul A'zam Gayo Lues Islamic Boarding School. The study employed a qualitative hermeneutic phenomenological approach with the Interpretative Phenomenological Analysis (IPA) method to deeply understand the participants' lived experiences. Participants consisted of one key informant and three students selected purposively. Data were collected through in-depth interviews, participant observation, and reflective notes, then analyzed through the identification of meaning units, the development of emergent themes, and cross-case synthesis. The results indicate that dzikir lata'if is interpreted as a reflective-contemplative process that encourages psychological transformation in four main dimensions: emotional regulation, cognitive clarity, behavioral self-control, and the development of empathy and prosocial orientation. These changes form a pattern of integrative consciousness characterized by inner calm, self-discipline, adaptive social relationships, and an increased sense of meaning in life. These findings suggest that structured spiritual practices can function as psycho-spiritual interventions that support holistic psychological development in the context of Islamic boarding school education. Keywords: dzikir lata'if; psychological meaning; integrative awareness; interpretive phenomenology; self-regulation